Synchrony in the onset of mental-state reasoning: Evidence from five cultures - Tara Callaghan (2018)
Over the past 20 years, developmental psychologists have shown considerable interest in the onset of a theory of mind, typically marked by children's ability to pass false-belief tasks. In Western cultures, children pass such tasks around the age of 5 years, with variations of the tasks producing small changes in the age at which they are passed. Knowing whether this age of transition is common across diverse cultures is important to understanding what causes this development. Cross-cultural studies have produced mixed findings, possibly because of varying methods used in different cultures. The present study used a single procedure to measure false-belief understanding in five cultures: Canada, India, Peru, Samoa, and Thailand. With a standardized procedure, we found synchrony in the onset of mentalistic reasoning, with children crossing the false-belief milestone at approximately 5 years of age in every culture studied. The meaning of this synchrony for the origins of mental-state understanding is discussed. Copyright © 2005 American Psychological Society.